CD74 auto-antibodies display little clinical value in Chinese Han population with axial spondyloarthritis. Issue 50 (11th December 2020) - Hu, Chao-Jun; Li, Meng-Tao; Li, Xi; Peng, Lin-Yi; Zhang, Shang-Zhu; Leng, Xiao-Mei; Su, Jin-Mei; Zeng, Xiao-Feng
Abstract : Abstract: The European cohort study has indicated about CD74 IgG-autoantibodies as potential marker for axial spondyloarthritis (axSpA) diagnosis. However, multiple studies have questioned the diagnostic value of various disease-specific autoantibodies in different ethnic groups. Here, we have tried to assess the diagnostic value of anti-CD74 IgG and IgA autoantibodies in axSpA patients from Chinese Han population. The anti-CD74 IgG and IgA autoantibodies were analyzed using ELISA assay in a cohort of 97 axSpA patients, including 47 treatment-naïve axSpA patients never treated with steroids or immunosuppressants and 50 treated axSpA patients. The rheumatic disease control (RDC) group consisted of 40 rheumatoid arthritis, 25 systemic lupus erythematosus, 18 psoriatic arthritis patients, and 60 healthy controls (HC). Our data demonstrated the presence of anti-CD74 IgA auto-antibodies in 25.8% of the axSpA patients, 30.1% of the RDC group patients and none in HC. Similarly, anti-CD74 IgG autoantibodies were observed in 23.7% of the axSpA patients, 18.1% of the RDC patients and 18.3% of the HC. The sensitivity, specificity, and accuracy of IgA autoantibodies were 21.3%, 82.5%, & 67.4%, respectively, while for IgG, it was 27.7%, 81.8%, and 68.4%, in treatment-naïve axSpA patients. Furthermore, weak positive relationship between anti-CD74 IgA autoantibodies and bath ankylosing spondylitis disease activity index ( r = 0.253, P = .012) and functional index (bath ankylosing spondylitis functional index; r = 0.257, P = .011) was observed. Overall, our study demonstrated little clinical and predictive value of CD74 autoantibodies in the diagnosis of axSpA and its related manifestations, among Chinese Han population.